Pelatihan Pengenalan Artificial Intelligence (AI) untuk Meningkatkan Kompetensi Guru pada Transformasi Digital - Nurul Anwar, Rosyida (Journal of Smart Community Service, 2024)
Digital technology enables various innovations in learning, such as adaptive learning, where learning content is adapted to the needs and abilities of each student. Monotonous learning causes boredom in students. Artificial Intelligence has great potential in supporting the teaching process for teachers and can increase teacher competence in learning. This community service activity aims to introduce teachers to Artificial Intelligence as part of digital transformation in education. The implementation method uses a capacity-building approach. The implementation stages include preparation, implementation, evaluation, and follow-up stages. The activity results show that teachers gain learning experience by utilizing Artificial Intelligence technology for an interesting and interactive learning process for students. Teachers can practice directly and know the technology that suits the characteristics of students. This community service activity increases teachers' professional competence in teaching.